Parasitic fauna of Mugil curema in a estuarine ecosystem in the northern coast of the Santa Catarina State, Brazil - Gueretz J.S. (2022)
© 2022, Archives of Veterinary Science.All Rights Reserved.Mugilids hold a characteristic parasitic fauna that varies according to the environment they live in. Epidemiological studies of this fauna are important for prophylaxis and treatment of zoonotic diseases. The aim of this study was to investigate the parasitic fauna of Mugil curema for 2 years, from November 2015 to October 2017, in estuarine waters of the Northshore of Santa Catarina. A total of 282 specimens were captured with a gillnet in the Parati River, Araquari, SC, Brazil. The fish were necropsied, and its parasitic fauna studied. Tha parasite prevalence rate was 96.81% (273/282), being 97.30% (72/74) females, 94.55% (52/55) males and 97.39% (149/153) nonidentified gender. The prevalence of Neoechinorhynchus curemai was 43.97% (124/282), Ergasilus lizae 77.66% (219/282), Lernaeenicus longiventris 73.05% (206/282), Ascocotyle (Phagicola) longa in the liver 24.04% (96/282) and in the muscle 36.88% (104/282), and Haloporidae was found in 26.13% (29/111). The Parati River has peculiar characteristics on its dynamics, which interferes in the parasitological rates of the fish living there, a relation that still needs better investigation